No. If you will transform both to the form y = mx + b, we should see whether they are equal or not.
x + y = -1 ---> y = -x - 1
2x + 3y = -4 ---> y = -(2/3)x - 4/3
Since both m, and b are different, then the 2 are definitely different from each other.
2007-02-28 02:36:11
·
answer #1
·
answered by Moja1981 5
·
1⤊
0⤋
If (x + y = -1) is true, > -2(x + y = -1) is true. > -2x - 2y = 2 is true
- 2x - 2y = 2
2x + 3y = -4 add
____________
0 + y = -2
x + y = - 1 (When y = -2) > x -2 = - 1 > x = 1
So x+ y = -1 is the same as 2x +3y = - 4
Only when x = 1 and y = -2
Check:
1 - 2 = -1 > - 1 = -1 right
2 - 6 = -4 > - 4 = -4 right
2007-02-28 11:30:18
·
answer #2
·
answered by robertonereo 4
·
0⤊
0⤋
No.
cuz in eq. 1 if u multiply it with anything the coefficients of x , y and the constant value will be equal
2007-02-28 10:57:48
·
answer #3
·
answered by Maths Rocks 4
·
0⤊
0⤋
Since the second equation is not a multiple of the first equation, they are not "the same".
2007-02-28 10:39:58
·
answer #4
·
answered by S. B. 6
·
0⤊
0⤋
No, there is no linear dependency between the two equations.
2007-02-28 10:36:20
·
answer #5
·
answered by Amit Y 5
·
0⤊
0⤋
No, if you put x as -0.5 and y as -0.5 you don't get the right answer for the second equation.
2007-02-28 10:35:42
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
it depends on ur x and y values trust me i noe i have algebra 2 everyday n skool
2007-02-28 10:39:18
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋
It could be.
It all depends on the values you put for x and y.
2007-02-28 10:34:38
·
answer #8
·
answered by Michael Dino C 4
·
0⤊
1⤋
no
2007-02-28 10:38:26
·
answer #9
·
answered by Rick 5
·
1⤊
0⤋
No, why?
2007-02-28 11:03:09
·
answer #10
·
answered by shrek 5
·
0⤊
0⤋